V. N. Strakhov's mounting approach to solving inverse problems of gravity prospecting: the current state and real possibilities - P. I. Balk; A. Yeske (Геофизический журнал, 2013)
Strakhov's mounting algorithms for solving nonlinear inverse gravity problems are considered from the point of view of the concept of problem-oriented methods of conditional minimization, which make up the core of any technology for quantitative interpretation of gravity data. The comparative analysis of editing algorithms has revealed their main advantage, which lies in the ability to bypass the richly "acute angles" in the theory and practice of interpretation of potential fields, have become a stumbling block for most known approaches to solving inverse problems, which rely on classical methods to solve the conditions of no-extremal problems . At the same time, the question of the actual resolution of the editing method remains unresolved, the answer to which can only be given by a large-scale computational experiment. In this article, this gap is partially filled.